(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
There are many difficulties in the process of studying and teaching English, especially medical topics, in medical institutions. The importance of understanding and proper use of terminology, science-related texts in English is growing in such institutions. The need to learn English is emerging in order to be integrated into World medicine and scientific progress, to participate in modern innovations, to improve qualifications and to make extensive use of experience learning opportunities abroad. However, there are also problems that students and teachers in this area face in the process of reading, understanding and mastering the news of medical texts in English in a small amount of time.